DETERMINATION OF AGE FROM SKELETAL STRUCTURES OF POMADASYS HASTA (BLOCH) - Nammalwar, p (Indian Journal of Fisheries, 2011)
Some skeletal stuctures like vertebrae, palatine, cleithrum and operculum appear to be useful in the determination of age of P. hasta. These parts have been found useful in determining age of fish by Hart (1950) Menon (1950) Pantulu (1961) and others. Le cren (1947) and Gosline (1960) studied the growth rings on bones for determining the age and growth rate of percoid fishes